2014
DOI: 10.1097/coc.0b013e318277d5f4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Comorbid Conditions on Survival in Endometrial Cancer

Abstract: In this study, DM and HTN adversely effected survival. Given the favorable survival rate for most patients with endometrial cancer, attention to comorbid conditions, and particularly DM and HTN, is becoming more relevant for its implications on current health care and policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 2 publications
1
41
0
2
Order By: Relevance
“…It should be considered that obesity itself (BMI >35 kg/m 2 ) plays a major confounding role because, in several studies, high BMI was an independent prognostic factor for the development of postoperative lymphedema (11,26,38).…”
Section: Incidencementioning
confidence: 99%
“…It should be considered that obesity itself (BMI >35 kg/m 2 ) plays a major confounding role because, in several studies, high BMI was an independent prognostic factor for the development of postoperative lymphedema (11,26,38).…”
Section: Incidencementioning
confidence: 99%
“…Black women have a higher prevalence of obesity, diabetes mellitus, and hypertension. 13 Although these conditions have been associated with poorer survival rates, 14 a recent report with the use of Surveillance, Epidemiology, and End Results (SEER) Medicare data illustrated that comorbid conditions do not account fully for the racial disparity that is seen in endometrial cancer survival in a Medicare population. 15 We sought to further evaluate the relationship between comorbid conditions and the racial disparity in endometrial cancer survival among women of all ages at a single institution.…”
mentioning
confidence: 99%
“…12 While obesity may put patients at higher risk of surgical morbidity, Temkin et al and Modesitt et al showed that it was not an independent predictor of progression or overall survival but likely related to other comorbid conditions. 20,21 Given the possibility of multi-collinearity between individual comorbid conditions and survival, the use of a standardized comorbidity index while studying survival in EC patients is more appropriate.…”
Section: Commentsmentioning
confidence: 99%
“…9–11 Nicholas and colleagues showed that a diagnosis of diabetes and/or hypertension in EC patients resulted in a decreased survival even after adjusting for age, stage and grade. 12 Truong and colleagues studied the effect of age, Karnofsky performance status and Charlson comorbidity score on the treatment, recurrence and survival of EC patients. 13 They found that advanced age was associated with a decline in prescribed postoperative radiation therapy.…”
Section: Introductionmentioning
confidence: 99%